2003
DOI: 10.1590/s0066-782x2003000400002
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal septal alcoholization for the treatment of refractory hypertrophic obstructive cardiomyopathy: initial experience in the Federal District

Abstract: Percutaneous transluminal septal alcoholization is effective and safe in the treatment of HOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We included all the case series published in English and the English versions of foreign case series when available. A total of 42 studies/case series 10–21,24–27,33–58 were included in the final review. Inclusion criteria in these studies included symptomatic HOCM despite reported medical therapy, persistence of symptoms after dual chamber sequential pacing, or surgical myomectomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included all the case series published in English and the English versions of foreign case series when available. A total of 42 studies/case series 10–21,24–27,33–58 were included in the final review. Inclusion criteria in these studies included symptomatic HOCM despite reported medical therapy, persistence of symptoms after dual chamber sequential pacing, or surgical myomectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol septal ablation (ASA) is a new catheter‐based intervention that has been used as an alternative to surgical septal reduction 10–16 . ASA is performed through a percutaneous approach, in which 1–3 cc of absolute ethanol is introduced into a major septal artery to create a controlled septal infarction and necrosis at the base of the hypertrophied interventricular septum 17–23 .…”
Section: Introductionmentioning
confidence: 99%
“…AF confers increased risk of all‐cause mortality, including that due to heart failure and thromboembolic events and is associated with worsened exercise capacity and symptoms impacting quality of life . Despite multiple cohort studies of patients undergoing ASA for symptomatic HCM, , none has reported on the incidence of AF. We evaluated the incidence of AF following ASA for symptomatic HCM.…”
mentioning
confidence: 99%